PREPARATION, DIELECTRIC AND OPTICAL PROPERTIES OF Cr2O3 /PVC NANOCOMPOSITE FILMS - Hassena, A.; El-Sayeda, S.; Morsic, W.M.; Sayedb, A.M. El (JOURNAL OF ADVANCES IN PHYSICS, 2014)
Chromium oxide (Cr2O3) nanoparticles were synthesized using a sol-gel method and mixed with polyvinyl chloride (PVC). Rietveld refinement of X-ray powder diffraction (XRD) patterns of the samples revealed that the crystal structure of Cr2O3 is rhombohedral with space symmetry group. Scanning electron microscopy images showed that the Cr2O3 nanoparticles are well dispersed on the surface of the PVC films. The dielectric permittivity (e’), and ac conductivity (Ïƒac) of pure PVC increased with adding Cr2O3 due to the formation of conductive three-dimensional networks throughout the nanocomposite films and interfacial polarizations. The optical energy band gap (Eg) of the films decreases with increasing Cr2O3 content. The refractive index dispersion of the nanocomposite films obeys the single oscillator model. The dispersion parameters are changed by incorporation of Cr2O3. The optical properties of PVC are influenced by addition of Cr2O3 nanoparticles.